Pembentukan Citra Satuan Polisi Pamong Praja: Studi Komunikasi Eksternal Kegiatan SatPol PP Kabupaten Deli Serdang di Masa Pandemi Covid-19 - Reza, Muhammad; Harahap, Nursapian (Medan Resource Center, 2022)
The purpose of this study was to determine how the image formation of the civil service police unit in the district of Deli Serdang The negative image attached to the Satpol PP must be removed immediately. The purpose of the study was to describe the activities of the Deli Serdang Regency Satpol PP in building an image in the eyes of the Deli Serdang community and the obstacles that arise in it. The research method used descriptive qualitative with steps of observation data analysis, interviews, data collection, data reduction, data presentation, and conclusions. The results of the study that the existence of the Head of Administration as the bearer of the task of Public Relations who is responsible for forming the image of the Satpol PP of Deli Serdang Regency is very necessary as an effort to be able to establish a good relationship with the public, and the inherent negative impression can be eroded along with good communication.